Design of an Illustrated Book “Something In To You” On the Importance of Self-Love to Enhance Self-Confidence Among Young Women in Bandung, Indonesia - Maeni, Purmaningrum; Alvitarisa Nadhiva, Auradyta; Firli, Herdiana (Universitas Pasundan, 2025)
Self-confidence is one of the most essential qualities every individual should possess. A common issue observedtoday is that many adolescents still struggle with low self-confidence in their daily lives. One of the main causesof low self-confidence is the lack of attention to oneself, or in other words, the lack of self-love. Self-love playsa crucial role in enabling individuals to live their lives in a more balanced manner. Loving oneself means valuingone’s well-being and personal happiness.The method used to address this issue is a qualitative approach, inwhich data were collected through literature studies, observations, and interviews with both the target audienceand experts. The findings indicate that individuals with a strong sense of self-love tend to be more confident,less affected by others’ negative opinions, and more capable of facing challenges with conviction. However, selflove also requires support from the surrounding environment, or at least a source of motivation that helpsindividuals rise again.Therefore, an illustrated book on the theme of self-love was designed to provide insightsand enhance self-confidence through the practice of loving oneself. The book contains guidance and methods onhow to manage and cultivate self-love, as many people still lack an understanding of how to implement it intheir lives. Through these illustrations, it is hoped that individuals experiencing self-doubt can learn to applyself-love and overcome their lack of confidence.